Navier-Stokes-based predictions of the aerodynamic behaviour of stall regulated wind turbines using OpenFOAM. (2016) - Rahimi, Hamid; Medjroubi, Wided; Stoevesandt, Bernhard; Peinke, Joachim
It is a challenging task to simulate the turbulent and separated flow around a rotating twisted wind turbine blade. In this study, the open source CFD package OpenFOAM was used in order to investigate the aerodynamics of the NREL phase VI rotor by solving the three-dimensional Reynolds averaged Navier-Stokes (RANS) equations. During this study, steady-state simulations for multiple upwind configurations of the wind tunnel experiment were conducted. The results are then shown in comparison with those obtained by other researchers and also measurements. For the purpose of verification and validation, aerodynamic key parameters such as power, thrust and pressure distributions at different spanwise sections along the blade are used. Furthermore, the quality of the mesh was verified by using a grid independence test based on the grid convergence index and grid resolution test. The results for a constant pitch at varying wind speeds showed that the present simulations consistently and accurately predicted the experimental data.